The Spiritual Turn: The Religion of the Heart and the Making of Romantic Liberal Modernity - Watts, Galen (Oxford University Press USA - OSO, 2022)
North Americans and Western Europeans increasingly identify as 'spiritual but not religious'. This book combines cultural sociology with intellectual history and political philosophy to examine this 'spiritual turn'.